Boom and Bust for Homocysteine? - Doherty, Gayle H. (Central Nervous System Agents in Medicinal Chemistry, 2008)
Just a few short years ago, elevated homocysteine levels were widely considered to be a risk factor for a plethora of diseases from cardiovascular disorders to neurodegenerative conditions. Because of this there was a boom in research into this amino acid, with over 13 000 scientific papers published on it by January, 2008. It was hoped that simple pharmacological and dietary intervention to lower plasma homocysteine would offer a cost-effective solution to prevent the future development of disease in individuals with high homocysteine levels. However, trials of vitamin therapies to counteract elevated homocysteine, whilst successful in lowering plasma homocysteine, have not demonstrated any clinical benefit. Thus, many now believe that it is possible that elevated homocysteine levels are a consequence of, rather than a cause of, cardiovascular and neurodegenerative disorders. If this is so, then the value of homocysteine as a target for research and pharmacological intervention is greatly reduced. So, is the boom time for homocysteine research over? This review will consider the scientific studies relating to homocysteine and neurodegenerative conditions, with particular reference to Alzheimer's Disease and Parkinson's Disease, and will consider what is next for homocysteine research.
Keywords: Alzheimer' s Disease